역행성 견관절 전치환술을 위한 인공관절 삽입 훈련 시뮬레이터 - 김수영(Su Young Kim); 고준호(Junho Ko); 장성욱(Seong-wook Jang); 유연식(Yon-Sik Yoo); 김윤상(Yoon Sang Kim) (디지털콘텐츠학회논문지, 2019)
기존의 인공관절 전치환술 시뮬레이터들은 대부분 고관절 및 슬관절 수술을 대상으로 하고 있으며, 역행성 견관절 전치환술을 위한 시뮬레이터 연구는 미흡한 실정이다. 따라서 본 논문에서는 역행성 견관절 전치환술을 위한 인공관절 삽입 훈련 시뮬레이터를 제안한다. 제안된 시뮬레이터는 상완골, 견갑골, 인공관절 모델에 기반하여 다양한 환경에서 인공관절을 삽입시키는 훈련 기능을 제공한다. 또한, 어깨 회전 운동 검사를 통해 훈련 결과를 피드백하는 기능을 제공한다. 훈련자는 제공되는 인공관절 삽입 훈련을 반복적으로 수행함으로써, 역행성 견관절 전치환술에 대한 숙련도를 향상시킬 수 있다. Most of the conventional arthroplasty simulators are targeting the hip and knee surgery. Whereas, it didn’t consider about the simulator of reverse total shoulder arthroplasty. In this paper, we propose a prosthesis insertion training simulator for reverse total shoulder arthroplasty. The proposed simulator provides training function to insert prosthesis in a variety of environments based on the humerus, scapula, prosthesis models. In addition it provides function to feedback training results through range of motion on shoulder. Trainee can improve surgical skill of reverse total shoulder arthroplasty by repeatedly performing the provived prosthesis insertion training. KCI Citation Count: 0